Hepatitis B seroprevalence among 5 to 6 years old children in the Philippines born prior to routine hepatitis B vaccination at birth - Anna Lena Lopez; Michelle Ylade; Jedas Veronica Daag; Amado O. Tandoc; Joseph Bonifacio; Patrick G. Sylim; Ava Kristy Sy; Rex Centeno; Vito Roque; Maria Joyce Ducusin (Taylor & Francis Group, 2018)
To assess the prevalence of hepatitis B in the Philippines, we conducted a cross-sectional study among 5 to 6 year old children born in 2007-2008, when the birth dose started to be implemented in the country. The study was conducted from 25 July to 22 October 2013 in 24 provinces and used a 3-stage cluster design and probability-proportional to size sampling. Blood was obtained and sera were tested for hepatitis B surface antigen (HBsAg). The survey included 2,769 children, of whom 26% received a timely birth dose (within 24 hours of birth) and 89% received 3 doses of the hepatitis B vaccine. Due to problems in the initial testing algorithm, only 2,407 sera were available for HBsAg testing, 20 (weighted%, 0.86%) were HBsAg positive. By immunization card and recall, among HBsAg positive children, 2 (weighted%, 20%) received a timely birth dose while 17 (weighted%, 85%) received 3 doses of the hepatitis B vaccine. The seroprevalence of HBsAg that we detected was lower than expected. However, there were several limitations in the field and in the laboratory that may have affected the representativeness of the results. Follow up studies need to be conducted to validate these results.